Using simple language to manage the recognition process - Lubjuhn, Julia [Verfasser]; Moraht, Katharina [Verfasser] (My University, 2017)
"German officialese is difficult enough for many native speakers to understand. How much harder must it be for migrants who are confronted with this kind of lan-guage within the process of seeking professional or oc-cupational recognition? This article describes both how the “Recognition in Germany” information portal uses simple language for the purposes of providing guidance and identifying occupational competencies, as well as the challenges associated with this approach." (author's abstract ; BIBB-Doku)
Mit Einfacher Sprache durch den beruflichen Anerkennungsprozess
Keywords: P 1.5 Migranten; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; Einfache Sprache; Migrant; Auslandsqualifikation; Anerkennung; Beratung